Perception Of Cataract Patients Regarding Health Care Services at Tertiary Care Hospital - Patel, Kunjan J; Kapadia, Priti R; Chaudhari, Vipul P; Patel, Nikunj V; Patel, Shivani D; Jindal, Akshita R (National Journal of Community Medicine, 2015)
Introduction: Cataract is the major cause of treatable blindness in India (62.6 %). The state of Gujarat is performing more than 100% of the target given by NPCB. Ophthalmic services in private setup are very costly. Government tertiary eye care centres are now well equipped. So assessing perception of patients is very important is- sues and that will help to improve the services. Objective of the study was to assess the perceptions of cataract patients about the health services. Method: This cross sectional study was carried out between August 2012 and October 2012 with purposive sampling of 300 cases. Results: 52.3% patients came here due to good quality service. Im- proved visual acuity is not necessarily the most important factor for patient satisfaction after cataract surgery as many patients are influ- enced by the care that is provided by medical (77.7%) and paramed- ical staff (57.6%). The out-patient department significantly affected the level of patient satisfaction. 80%were satisfied with overall eye care services provide at hospital and 88.3% cases would recommend others to take eye care services at this centre. Conclusions: Highly competent and professional healthcare person- nel are required for providing highest quality and satisfaction to the patients.